A particulate whisker hybrid reinforced wear resistant copper alloy and a method of making the same

CN122879620APending Publication Date: 2026-10-09NORTH CHINA ELECTRIC POWER UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611290797.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

基于上述因素,使得合金力学性能大大降低,限制了Cu-Ni-Si-Ti合金的工业应用

Benefits of technology

本发明提供的颗粒晶须混杂增强耐磨铜合金(Sr变质的颗粒晶须混杂增强铜合金)变质效果显著且双重优化:Sr元素的添加有效细化了初生Ni16Ti6Si7颗粒,使其平均直径从变质前的7~9μm降低至4~6μm,同时显著改善了共晶NiTiSi晶须的形貌与尺寸,使其从粗大针状转变为更为细密、圆钝的短棒状或簇状,直径从变质前的600nm~800nm降低至300~500nm,长度也有所减少,达到了2~10μm,实现了对颗粒和晶须两种增强相的同步优化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879620A_ABST
    Figure CN122879620A_ABST
Patent Text Reader

Abstract

This invention belongs to the field of alloy materials technology, and more specifically relates to a wear-resistant copper alloy reinforced with a mixture of grain whiskers and its preparation method. It addresses the issue of primary Ni in existing Cu-Ni-Si-Ti alloys. 16 The large size and uneven distribution of Ti6Si7 particles and eutectic NiTiSi whiskers lead to insufficient mechanical properties and wear resistance of the alloy. This invention addresses this issue by introducing a Cu-Sr master alloy during the alloy smelting process to perform Sr modification treatment, thereby improving the Sr content of the primary Ni... 16 Ti6Si7 particles and eutectic NiTiSi whiskers undergo modification and significant refinement. The results show that after Sr modification treatment, the primary Ni... 16 The average diameter of Ti6Si7 particles and NiTiSi whiskers are significantly reduced, resulting in a more rounded and uniform morphology and significantly improved tribological properties of copper alloys. The modification process described in this invention is simple and stable, requires extremely low Sr element addition, and has controllable costs, making it suitable for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of alloy materials technology, and more specifically relates to a wear-resistant copper alloy reinforced with mixed grain whiskers and its preparation method. Background Technology

[0002] Copper-based materials, with their excellent comprehensive properties, have become indispensable strategic materials for key components in fields such as machinery manufacturing, rail transportation, high-voltage electrical appliances, and weaponry. As related equipment continues to develop towards high speed, heavy load, and high reliability, their service conditions are becoming increasingly demanding, placing higher requirements on the mechanical properties, wear resistance, high-temperature stability, and service reliability of copper-based materials. Among currently common high-performance wear-resistant copper-based materials, one of the main technical approaches to improving performance is the introduction of high-hardness, high-thermal-stability ceramic reinforcing phases (such as particles, whiskers, etc.) to prepare copper-based composite materials with a second-phase strengthening effect.

[0003] Among them, the particle-whisker hybrid reinforcement system has attracted much attention due to its ability to synergistically exert multiple strengthening mechanisms: compared with copper alloys reinforced by single particles or whiskers, the particle-reinforcing phase improves the overall strength of the matrix and adjusts the spatial distribution of whiskers; the whisker-reinforcing phase refines the grains and bears a large amount of average stress, playing a role in load transfer in the matrix, improving the strength and toughness of the composite material. The synergistic effect of the two improves the tribological properties of copper-based composite materials. By optimizing the type, morphology, size, spatial distribution, and interfacial bonding state with the matrix of the two types of reinforcing phases, further breakthroughs in material properties are expected. Cu-Ni-Si-Ti alloy is a commonly used particle-whisker hybrid reinforcement system copper alloy.

[0004] However, in the microstructure of Cu-Ni-Si-Ti alloys, primary Ni 16 Ti6Si7 particles and eutectic NiTiSi whiskers typically appear in a coarse and irregular state. The coarse particles are not coordinated with the matrix deformation, easily leading to crack initiation and propagation at the interface. Simultaneously, the coarse, needle-like whiskers in the microstructure severely rupture the matrix, often being the main cause of crack initiation, propagation, and material failure. These factors significantly reduce the mechanical properties of the alloy, limiting its industrial application.

[0005] Therefore, how to propose a modification treatment method for Cu-Ni-Si-Ti copper alloys reinforced with mixed particles and whiskers, which can fully utilize the synergistic reinforcement effect of particles and whiskers by optimizing the structure and distribution of the reinforcing phase, and thus prepare copper-based composite materials with higher strength, better wear resistance and better reliability to meet the growing application needs of high-end equipment fields, has become a problem that urgently needs to be solved by those skilled in the art. Summary of the Invention

[0006] The purpose of this invention is to provide a particle-whisker hybrid reinforced wear-resistant copper alloy and its preparation method. Specifically, a modification treatment method for a particle-whisker hybrid reinforced wear-resistant copper alloy is used to prepare an Sr-modified particle-whisker hybrid reinforced copper alloy, which has excellent comprehensive properties, high strength, high toughness, and superior friction and wear resistance. This method is simple and easy to implement, thus solving the problems existing in the prior art.

[0007] To achieve the above objectives, the present invention provides the following solution: One of the technical solutions of this invention: provides a wear-resistant copper alloy reinforced with mixed grain whiskers, the composition of which, by mass percentage, includes: Ni 1.0~6.0%, Si 0.2~1.5%, Ti 0.7~2% and Sr 0.01~0.20%, with the balance being Cu and unavoidable impurity elements.

[0008] The second technical solution of this invention provides a method for preparing a wear-resistant copper alloy reinforced with mixed grain whiskers, comprising the following steps: Prepare high-purity copper (purity ≥ 99.99%), high-purity nickel (purity ≥ 99.9%), high-purity silicon (purity ≥ 99.99%), sponge titanium (TA1), and Cu-20Sr master alloy as raw materials according to the above mass percentages; Under argon protection and charcoal covering, the high-purity copper is smelted and completely melted. High-purity nickel is then added for a first heat preservation treatment, followed by cooling to a first preset temperature. High-purity silicon, sponge titanium, and Cu-20Sr master alloy are then added for a second heat preservation treatment. After the heat preservation is completed, the wear-resistant copper alloy with mixed granular whiskers is cast.

[0009] Furthermore, the melting process is carried out at a temperature of 1150~1350℃.

[0010] Furthermore, the temperature of the first heat preservation treatment is 1300~1350℃, and the time is 3~5 minutes.

[0011] Furthermore, the first preset temperature is 1275~1300℃.

[0012] Furthermore, the cooling rate to the first preset temperature is 15~25℃ / min.

[0013] Furthermore, the temperature of the second heat preservation treatment is 1280~1320℃, and the time is 1~2 minutes.

[0014] Furthermore, the process of deoxidation and slag removal is also included after the high-purity copper is completely melted or before casting.

[0015] Optionally, the deoxidation and slag removal treatment involves adding cryolite to the melt for deoxidation and slag removal, with the amount of cryolite added being 0.2 to 0.4% of the total mass of the melt.

[0016] Furthermore, the mold used for casting is a graphite mold, and the preheating temperature of the graphite mold is 200°C.

[0017] The third technical solution of this invention: provides a modification treatment method for a wear-resistant copper alloy reinforced with mixed grain whiskers, the steps of which include: Prepare high-purity copper (purity ≥ 99.99%), high-purity nickel (purity ≥ 99.9%), high-purity silicon (purity ≥ 99.99%), sponge titanium (TA1), and Cu-20Sr master alloy as raw materials; Under argon protection and charcoal covering, the high-purity copper is smelted. After complete melting, high-purity nickel is added for the first heat preservation treatment. Then, it is cooled to the first preset temperature. High-purity silicon, sponge titanium and Cu-20Sr master alloy are added for the second heat preservation treatment. After the heat preservation is completed, deoxidation and slag removal treatment is performed, and Sr-modified granular whisker mixed reinforced copper alloy is cast. The composition of the Sr-modified granular whisker-reinforced copper alloy, by mass percentage, includes: Ni 1.0~6.0%, Si 0.2~1.5%, Ti 0.7~2% and Sr 0.01~0.20%, with the balance being Cu and unavoidable impurity elements.

[0018] Furthermore, the melting process is carried out at a temperature of 1150~1350℃.

[0019] Furthermore, the temperature of the first heat preservation treatment is 1300~1350℃, and the time is 3~5 minutes.

[0020] Furthermore, the first preset temperature is 1275~1300℃.

[0021] Furthermore, the cooling rate to the first preset temperature is 15~25℃ / min.

[0022] Furthermore, the temperature of the second heat preservation treatment is 1280~1320℃, and the time is 1~2 minutes.

[0023] Furthermore, the process of deoxidation and slag removal is also included after the high-purity copper is completely melted or before casting.

[0024] Optionally, the deoxidation and slag removal treatment involves adding cryolite to the melt for deoxidation and slag removal, with the amount of cryolite added being 0.2 to 0.4% of the total mass of the melt.

[0025] Furthermore, the mold used for casting is a graphite mold, and the preheating temperature of the graphite mold is 200°C.

[0026] The present invention discloses the following technical effects: The wear-resistant copper alloy reinforced with mixed grain whiskers provided by this invention (Sr-modified mixed grain whisker reinforced copper alloy) exhibits significant modification effects and dual optimization: the addition of Sr element effectively refines the primary Ni... 16 The Ti6Si7 particles reduced the average diameter from 7-9 μm before metamorphism to 4-6 μm, while significantly improving the morphology and size of the eutectic NiTiSi whiskers, transforming them from coarse needle-like structures into finer, rounded short rod-like or cluster-like structures. The diameter decreased from 600-800 nm before metamorphism to 300-500 nm, and the length also decreased to 2-10 μm, achieving simultaneous optimization of both the particle and whisker reinforcing phases.

[0027] The wear-resistant copper alloy (Sr-modified granular whisker-reinforced copper alloy) provided by this invention exhibits significantly improved mechanical and physical properties: thanks to the refinement and uniform distribution of the reinforcing phase, the mechanical properties of the alloy are significantly improved after modification. Its tensile strength increases from 326.05 MPa before modification to 391.61 MPa, an increase of approximately 20%; its microVickers hardness increases from 103.84 HV to 145.52 HV, an increase of approximately 40%. Simultaneously, the alloy maintains good electrical conductivity and excellent high-temperature softening resistance, with a high-temperature softening resistance exceeding 450℃.

[0028] The method for preparing a grain-whisker hybrid reinforced wear-resistant copper alloy (Sr-modified grain-whisker hybrid reinforced copper alloy) provided by this invention is simple, low-cost, and suitable for industrialization. The method described in this invention has a concise process flow, a wide process window, and stable operation. Most importantly, the Sr element is added in the form of an intermediate alloy at an extremely low dosage, and the charcoal covering significantly reduces oxidation during the smelting process, avoiding complex vacuum equipment and greatly reducing production costs, making it suitable for large-scale industrial production. Attached Figure Description

[0029] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 This is a scanning electron microscope image of the as-cast microstructure of the wear-resistant copper alloy reinforced with mixed grain whiskers in Example 1.

[0030] Figure 2 This is a scanning electron microscope (SEM) image of the deep corrosion microstructure of the wear-resistant copper alloy reinforced with mixed grain whiskers in Example 1.

[0031] Figure 3This is a scanning electron microscope (SEM) image of the as-cast microstructure of the wear-resistant copper alloy reinforced with mixed grain whiskers in Example 2.

[0032] Figure 4 This is a scanning electron microscope (SEM) image of the deep corrosion microstructure of the wear-resistant copper alloy reinforced with mixed grain whiskers in Example 2.

[0033] Figure 5 The image shows a scanning electron microscope (SEM) image of the as-cast microstructure of the Sr-free, grain-whisker-reinforced copper alloy in Comparative Example 1.

[0034] Figure 6 The image shows a scanning electron microscope (SEM) image of the as-cast microstructure of the Sr-free, grain-whisker-reinforced copper alloy in Comparative Example 2.

[0035] Figure 7 The image shows a scanning electron microscope (SEM) image of the as-cast microstructure of the copper alloy reinforced with grain whiskers modified by excess Sr element in Comparative Example 3.

[0036] Figure 8 The image shows a scanning electron microscope (SEM) image of the as-cast microstructure of the Sr-modified particle whisker-reinforced copper alloy with altered material addition order in Comparative Example 4.

[0037] Figure 9 This is a scanning electron microscope image of the as-cast microstructure of the copper alloy in Comparative Example 5. Detailed Implementation

[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0039] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0040] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0041] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0042] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0043] Unless otherwise specified, all raw materials and reagents involved in the specific embodiments of this invention are commercially available products.

[0044] Unless otherwise specified, room temperature and normal temperature in the specific embodiments of this invention refer to 20-30℃.

[0045] Unless otherwise specified, the natural cooling involved in the specific embodiments of the present invention refers to furnace cooling during the smelting process, with a cooling rate between 15 and 25°C / min.

[0046] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.

[0047] In some specific embodiments, the present invention provides a method for preparing a wear-resistant copper alloy reinforced with mixed grain whiskers, the steps of which include: S1. Prepare high-purity copper (purity ≥ 99.99%), high-purity nickel (purity ≥ 99.9%), high-purity silicon (purity ≥ 99.99%), sponge titanium (TA1), and Cu-20Sr master alloy as raw materials according to the following mass percentages; Ni 1.0~6.0%, Si 0.2~1.5%, Ti 0.7~2% and Sr 0.01~0.20%, with the balance being Cu and unavoidable impurity elements.

[0048] S2. High-purity copper is placed in a medium-frequency induction furnace for smelting (1150~1350℃). An appropriate amount of charcoal is added to cover the surface of the melt, and Ar gas is continuously introduced for protection to prevent oxidation of the melt. After the high-purity copper is completely melted, high-purity nickel is added, and the temperature is held at 1300~1350℃ for 3~5 minutes (first holding treatment). Then, it is naturally cooled to 1275~1300℃. High-purity silicon, sponge titanium, and Cu-20Sr master alloy are added in sequence, and the temperature is held at 1280~1320℃ for 1~2 minutes (second holding treatment to ensure uniform distribution of Sr elements and full play of modification effect). After the holding is completed, the melt is cast into a graphite mold preheated to 200℃. After solidification, a grain whisker-reinforced wear-resistant copper alloy (Sr modified Cu-Ni-Si-Ti alloy ingot) is obtained. After the pure copper is completely melted or before casting, a deoxidation and slag removal process is also included: cryolite is added to the melt, stirred thoroughly, and then the slag is removed. The amount of cryolite added is 0.2 to 0.4% of the total mass of the melt.

[0049] For the primary Ni in existing Cu-Ni-Si-Ti alloys 16 The large size and uneven distribution of Ti6Si7 particles and eutectic NiTiSi whiskers lead to insufficient mechanical properties and wear resistance of the alloy. This invention addresses this issue by introducing a Cu-Sr master alloy during the alloy smelting process to perform Sr modification treatment, thereby improving the Sr content of the primary Ni... 16 Ti6Si7 particles and eutectic NiTiSi whiskers undergo modification and significant refinement. The results show that after Sr modification treatment, the primary Ni... 16 The average diameter of Ti6Si7 particles is significantly reduced from 7-9 μm before modification to 4-6 μm, and the average diameter of NiTiSi whiskers is reduced from 600-800 nm to 300-500 nm. Their morphology is more rounded and their distribution more uniform, significantly improving the tribological properties of copper alloys. The modification process described in this invention is simple and stable, requires extremely low Sr element addition, and has controllable costs, making it suitable for industrial application.

[0050] The present invention uses a first heat preservation treatment to ensure that the added pure Ni is fully dissolved so that it can form a uniform and stable Cu-Ni-Si-Ti alloy melt with Si and Ti during subsequent heating.

[0051] This invention utilizes a second heat preservation treatment to allow Sr elements to diffuse fully, thereby maximizing the remodeling effect of Sr and transforming the nascent Ni. 16 Refinement of Ti6Si7 particles and eutectic NiTiSi whiskers.

[0052] The present invention preferably involves adding charcoal for covering and purging with Ar gas to protect the melt during the preparation of Sr-modified Cu-Ni-Si-Ti alloy ingots. This achieves atmospheric melting while avoiding the introduction of impurities, making it suitable for large-scale industrial production.

[0053] This invention involves adding cryolite after pure copper has been completely melted or before casting for deoxidation and slag removal. This effectively avoids the generation of oxides during the smelting process. By deoxidizing and removing slag, impurities are removed, the purity of the copper alloy is improved, and the overall performance of Sr-modified Cu-Ni-Si-Ti alloy ingots is enhanced.

[0054] In summary, the preparation method provided by this invention is a modification treatment method for wear-resistant copper alloys reinforced with mixed grain whiskers. Through alloying design of Ni, Si, Ti, and Sr elements, it significantly improves the primary Ni... 16 The size, morphology and distribution of Ti6Si7 particles and eutectic NiTiSi whiskers were studied to prepare Sr-modified particle whisker hybrid reinforced copper alloy with synergistic reinforcement of particles and whiskers of different dimensions. The casting process in this invention is simple and stable, with low preparation cost. After adding charcoal cover, it can be smelted in the atmosphere, which is suitable for large-scale industrial production.

[0055] Example 1 The preparation steps of wear-resistant copper alloy reinforced with mixed grain whiskers include: S1. Prepare high-purity copper (purity ≥ 99.99%), high-purity nickel (purity ≥ 99.9%), high-purity silicon (purity ≥ 99.99%), sponge titanium (TA1), and Cu-20Sr master alloy as raw materials according to the following mass percentages; Ni 3.20%, Si 0.67%, Ti 0.98% and Sr 0.10%, with the balance being Cu and unavoidable impurity elements.

[0056] S2. High-purity copper is placed in a medium-frequency induction furnace for smelting (1200℃). An appropriate amount of charcoal is added to cover the surface of the melt, and Ar gas is continuously introduced for protection to prevent oxidation of the melt. After the high-purity copper is completely melted, high-purity nickel is added, and the temperature is held at 1350℃ for 4 minutes. Then, it is naturally cooled to 1290℃. High-purity silicon, sponge titanium, and Cu-20Sr master alloy are added in sequence, and the temperature is held at 1320℃ for 2 minutes. After the holding period, cryolite accounting for 0.3% of the total mass of the melt is added to the melt for deoxidation and slag removal. After thorough stirring, the slag is removed, and the melt is cast into a graphite mold preheated to 200℃. After solidification, a grain whisker-reinforced wear-resistant copper alloy (Sr modified Cu-Ni-Si-Ti alloy ingot) is obtained.

[0057] Example 2 The preparation steps of wear-resistant copper alloy reinforced with mixed grain whiskers include: S1. Prepare high-purity copper (purity ≥ 99.99%), high-purity nickel (purity ≥ 99.9%), high-purity silicon (purity ≥ 99.99%), sponge titanium (TA1), and Cu-20Sr master alloy as raw materials according to the following mass percentages; Ni 4.84%, Si 1.006%, Ti 1.47% and Sr 0.1%, with the balance being Cu and unavoidable impurity elements.

[0058] S2. High-purity copper is placed in a medium-frequency induction furnace for smelting (1200℃). An appropriate amount of charcoal is added to cover the surface of the melt, and Ar gas is continuously introduced for protection to prevent oxidation of the melt. After the high-purity copper is completely melted, high-purity nickel is added, and the temperature is held at 1350℃ for 4 minutes. Then, it is naturally cooled to 1290℃. High-purity silicon, sponge titanium, and Cu-20Sr master alloy are added in sequence, and the temperature is held at 1320℃ for 2 minutes. After the holding period, cryolite accounting for 0.3% of the total mass of the melt is added to the melt for deoxidation and slag removal. After thorough stirring, the slag is removed, and the melt is cast into a graphite mold preheated to 200℃. After solidification, a grain whisker-reinforced wear-resistant copper alloy (Sr modified Cu-Ni-Si-Ti alloy ingot) is obtained.

[0059] Comparative Example 1 The preparation steps for Sr-free grain whisker-reinforced copper alloys include: S1. Weigh out high-purity copper, high-purity nickel, high-purity silicon, and sponge titanium as raw materials in a mass ratio of 95.15:3.20:0.67:0.98 respectively. S2. High-purity copper is placed in a medium-frequency induction furnace for smelting (1200℃). An appropriate amount of charcoal is added to cover the surface of the melt, and Ar gas is continuously introduced for protection to prevent oxidation of the melt. After the high-purity copper is completely melted, high-purity nickel is added, and the melt is held at 1350℃ for 4 minutes. Then it is naturally cooled to 1290℃, and high-purity silicon and sponge titanium are added in sequence. The melt is then held at 1320℃ for 2 minutes to form a Cu-Ni-Si-Ti alloy melt. After the holding period, cryolite accounting for 0.3% of the total mass of the melt is added to the melt for deoxidation and slag removal. After thorough stirring, the slag is removed, and the melt is cast into a graphite mold preheated to 200℃. After solidification, a granular whisker-reinforced copper alloy without Sr element is obtained.

[0060] Comparative Example 2 The preparation steps for Sr-free grain whisker-reinforced copper alloys include: S1. Weigh out high-purity copper, high-purity nickel, high-purity silicon, and sponge titanium as raw materials according to the mass ratio of 92.684:4.84:1.006:1.47 respectively; S2. High-purity copper is placed in a medium-frequency induction furnace for smelting (1200℃). An appropriate amount of charcoal is added to cover the surface of the melt, and Ar gas is continuously introduced for protection to prevent oxidation of the melt. After the high-purity copper is completely melted, high-purity nickel is added, and the melt is held at 1350℃ for 4 minutes. Then it is naturally cooled to 1290℃, and high-purity silicon and sponge titanium are added in sequence. The melt is then held at 1320℃ for 2 minutes to form a Cu-Ni-Si-Ti alloy melt. After the holding period, cryolite accounting for 0.3% of the total mass of the melt is added to the melt for deoxidation and slag removal. After thorough stirring, the slag is removed, and the melt is cast into a graphite mold preheated to 200℃. After solidification, a granular whisker-reinforced copper alloy without Sr element is obtained.

[0061] Comparative Example 3 The preparation steps of copper alloy reinforced with granular whiskers modified by excess Sr element include: S1. Prepare high-purity copper, high-purity nickel, high-purity silicon, sponge titanium, and Cu-20Sr master alloy as raw materials according to the following mass percentages; Ni 3.20%, Si 0.86%, Ti 1.00% and Sr 0.30%, with the balance being Cu and unavoidable impurity elements.

[0062] S2. High-purity copper is placed in a medium-frequency induction furnace for smelting (1200℃). An appropriate amount of charcoal is added to cover the surface of the melt, and Ar gas is continuously introduced for protection to prevent oxidation of the melt. After the high-purity copper is completely melted, high-purity nickel is added, and the melt is held at 1350℃ for 4 minutes. Then, it is naturally cooled to 1290℃. High-purity silicon, sponge titanium, and Cu-20Sr master alloy are added in sequence, and the melt is held at 1320℃ for 2 minutes. After the holding period, cryolite accounting for 0.3% of the total mass of the melt is added to the melt for deoxidation and slag removal. After thorough stirring, the slag is removed, and the melt is cast into a graphite mold preheated to 200℃. After solidification, a copper alloy with granular whisker hybrid reinforcement and excess Sr element modification is obtained.

[0063] Comparative Example 4 The preparation steps of Sr modified grain whisker hybrid reinforced copper alloy with altered material addition order include: S1. Prepare high-purity copper, high-purity nickel, high-purity silicon, sponge titanium, and Cu-20Sr master alloy as raw materials according to the following mass percentages; Ni 3.20%, Si 0.67%, Ti 0.98% and Sr 0.1%, with the balance being Cu and unavoidable impurity elements.

[0064] S2. High-purity copper is placed in a medium-frequency induction furnace for smelting (1200℃). An appropriate amount of charcoal is added to cover the surface of the melt, and Ar gas is continuously introduced for protection to prevent oxidation of the melt. After the high-purity copper is completely melted, high-purity nickel, high-purity silicon, and sponge titanium are added to form a Cu-Ni-Si-Ti alloy melt. The melt is held at 1350℃ for 4 minutes, and then naturally cooled to 1290℃. Cu-20Sr master alloy is then added, and the melt is held at 1320℃ for 2 minutes. After the holding period, cryolite accounting for 0.3% of the total mass of the melt is added to the melt for deoxidation and slag removal. After thorough stirring, the slag is removed, and the melt is cast into a graphite mold preheated to 200℃. After solidification, a Sr modified particle whisker mixed reinforced copper alloy with altered material addition order is obtained.

[0065] Comparative Example 5 The preparation steps for low-Ti-content copper alloys include: S1. Prepare high-purity copper, high-purity nickel, high-purity silicon, sponge titanium, and Cu-20Sr master alloy as raw materials according to the following mass percentages; Ni 3.20%, Si 0.71%, Ti 0.5% and Sr 0.1%, with the balance being Cu and unavoidable impurity elements.

[0066] S2. Place high-purity copper in a medium-frequency induction furnace for smelting (1200℃). Add an appropriate amount of charcoal to cover the surface of the melt and continuously purge Ar gas to prevent oxidation of the melt. After the high-purity copper is completely melted, add high-purity nickel and hold at 1350℃ for 4 minutes. Then, let it cool naturally to 1290℃. Next, add high-purity silicon, sponge titanium and Cu-20Sr master alloy in sequence and hold at 1320℃ for 2 minutes. After holding, add cryolite accounting for 0.3% of the total mass of the melt to the melt for deoxidation and slag removal. After thorough stirring, remove the slag and cast the melt into a graphite mold preheated to 200℃. After solidification, a copper alloy is obtained.

[0067] Test case Figure 1 This is a scanning electron microscope (SEM) image of the as-cast microstructure of the wear-resistant copper alloy reinforced with mixed grain whiskers in Example 1.

[0068] Figure 2 This is a scanning electron microscope (SEM) image of the deep corrosion microstructure of the wear-resistant copper alloy reinforced with mixed grain whiskers in Example 1.

[0069] Depend on Figures 1-2 It can be seen that the primary Ni in the alloy 16 The Ti6Si7 particles are uniformly distributed and have a regular morphology, with an average diameter of about 3.24 μm and a volume fraction of about 3.296%. The eutectic NiTiSi whiskers are fine, short rod-shaped phases with an average diameter of about 0.43 μm and an average length of about 6.34 μm.

[0070] Performance test results show that the alloy has a hardness of 144.92 HV, a conductivity of 42% IACS, and a friction coefficient of 0.3201 with Cr15 steel.

[0071] Figure 3 This is a scanning electron microscope (SEM) image of the as-cast microstructure of the wear-resistant copper alloy reinforced with mixed grain whiskers in Example 2.

[0072] Figure 4 This is a scanning electron microscope (SEM) image of the deep corrosion microstructure of the wear-resistant copper alloy reinforced with mixed grain whiskers in Example 2.

[0073] Depend on Figures 3-4 It can be seen that under this composition, the primary Ni 16 The average diameter of the Ti6Si7 particles is approximately 3.75 μm, with a volume fraction increasing to approximately 5.403%; the average diameter of the eutectic NiTiSi whiskers is approximately 0.28 μm, and the average length is approximately 3.59 μm. This example demonstrates that even at a high volume fraction of the reinforcing phase, Sr modification can still effectively control its size and morphology, proving the good adaptability of the process of this invention to different component ratios.

[0074] Figure 5 The image shows a scanning electron microscope (SEM) image of the as-cast microstructure of the Sr-free, grain-whisker-reinforced copper alloy in Comparative Example 1. As can be seen from the image, compared to Example 1, the Ni content in the Sr-free, grain-whisker-reinforced copper alloy prepared in Comparative Example 1 is significantly lower. 16 The Ti6Si7 grain size increased significantly, with an average diameter of 5.24 μm and a volume fraction of 3.854%. The eutectic NiTiSi whiskers were relatively coarse, with an average diameter of approximately 0.56 μm and an average length of approximately 6.82 μm. Performance tests showed a hardness of 102.63 HV, a conductivity of 39% IACS, and a coefficient of friction of 0.4127 with Cr15 steel. In contrast, the alloy exhibited a coarser microstructure, irregular shape, and decreased alloy properties. This clearly demonstrates the significant modification effect of Sr.

[0075] Figure 6 The image shows a scanning electron microscope (SEM) image of the as-cast microstructure of the Sr-free, grain-whisker-reinforced copper alloy in Comparative Example 2. As can be seen from the image, even at high alloy contents, without Sr modification, Ni... 16 The average diameter of Ti6Si7 particles reached 4.65 μm, with a volume fraction of 7.354%; the average diameter of NiTiSi whiskers was 0.36 μm, and the average length was 4.36 μm. Compared with Example 2, this further verifies the key role of Sr modification in suppressing the coarsening of the reinforcing phase and optimizing the microstructure distribution.

[0076] Figure 7The image shows a scanning electron microscope (SEM) image of the as-cast microstructure of the granular whisker-reinforced copper alloy modified with excess Sr in Comparative Example 3. As can be seen from the image, even at high alloy contents, with excess Sr modification, Ni... 16 The Ti6Si7 particles had an average diameter of 3.52 μm and a volume fraction of 4.065%; the NiTiSi whiskers had an average diameter of 0.52 μm and an average length of 6.56 μm. Meanwhile, a brittle Cu5Sr phase was found in the alloy microstructure. Compared to Example 2, excessive Sr led to a decrease in the modification effect and the formation of a brittle phase that impaired the alloy's properties, hindering microstructure optimization.

[0077] Figure 8 This is a scanning electron microscope (SEM) image of the as-cast microstructure of the Sr-modified grain whisker-reinforced copper alloy with altered material addition order in Comparative Example 4. As shown in the figure, compared to Example 1, after changing the material addition order, the primary Ni in the alloy... 16 The Ti6Si7 particles exhibited significant agglomeration, with a volume fraction of approximately 3.583%. The uniformity of the eutectic NiTiSi whisker phase distribution was reduced, while the average diameter and average length remained essentially unchanged compared to before the material addition order was altered. Performance testing results showed that the alloy achieved a hardness of 148.39 HV, a conductivity of 40% IACS, and a coefficient of friction of 0.3538 with Cr15 steel. Compared to Example 1, due to the hard reinforcing phase Ni... 16 The increase in the volume fraction of Ti6Si7 phase slightly improves the hardness, but the conductivity decreases due to the poor uniformity of phase distribution, and the friction and wear coefficient also increases.

[0078] Figure 9 The image shows a scanning electron microscope (SEM) image of the as-cast microstructure of the copper alloy in Comparative Example 5. As can be seen from the image, compared to Example 1, when the Ti element added to the reinforcing phase was reduced from 0.98% to 0.5% by mass, the eutectic NiTiSi whisker phase in the alloy disappeared, and the reinforcing phase consisted only of primary Ni. 16 Ti6Si7 particles are uniformly distributed in the matrix. Performance test results show that the alloy has a hardness of 159.64 HV, a conductivity of 32% IACS, and a coefficient of friction of 0.3822 with Cr15 steel. Compared with Example 1, since the reinforcing phase is only the hard phase Ni... 16 Ti6Si7 exhibits significantly improved hardness and a marked decrease in conductivity; however, due to the disappearance of the whisker phase in the matrix, it cannot effectively transfer loads, resulting in a significantly increased coefficient of friction and wear.

[0079] By comparing the above embodiments and comparative examples, it can be found that the present invention, through the introduction of trace amounts of Sr element for modification treatment, can significantly optimize the primary Ni in Cu-Ni-Si-Ti alloys. 16This method involves analyzing the size, morphology, and distribution of Ti6Si7 particles and eutectic NiTiSi whiskers to prepare Sr-modified particle-whisker hybrid reinforced copper alloys with uniform microstructure and significantly improved strength, hardness, and wear resistance. The method is simple, low-cost, and has significant industrial application value.

[0080] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.

[0081] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A wear-resistant copper alloy reinforced with a mixture of grain whiskers, characterized in that, By weight percentage, the ingredients include: Ni 1.0~6.0%, Si 0.2~1.5%, Ti 0.7~2% and Sr 0.01~0.20%, with the balance being Cu and unavoidable impurity elements.

2. A method for preparing a wear-resistant copper alloy reinforced with mixed grain whiskers, characterized in that the steps include... include: According to the mass percentage of the particle whisker hybrid reinforced wear-resistant copper alloy described in claim 1, high-purity copper, high-purity nickel, high-purity silicon, sponge titanium, and Cu-20Sr master alloy are prepared as raw materials. Under argon protection and charcoal covering, the high-purity copper is smelted and completely melted. High-purity nickel is then added for a first heat preservation treatment, followed by cooling to a first preset temperature. High-purity silicon, sponge titanium, and Cu-20Sr master alloy are then added for a second heat preservation treatment. After the heat preservation is completed, the wear-resistant copper alloy with mixed granular whiskers is cast.

3. The preparation method according to claim 2, characterized in that, The smelting temperature is 1150~1350℃.

4. The preparation method according to claim 2, characterized in that, The temperature of the first heat preservation treatment is 1300~1350℃, and the time is 3~5 minutes.

5. The preparation method according to claim 2, characterized in that, The first preset temperature is 1275~1300℃.

6. The preparation method according to claim 2, characterized in that, The cooling rate to the first preset temperature is 15~25℃ / min.

7. The preparation method according to claim 2, characterized in that, The second heat preservation treatment is performed at a temperature of 1280~1320℃ for 1~2 minutes.

8. The preparation method according to claim 2, characterized in that, The process also includes deoxidation and slag removal after the high-purity copper is completely melted or before casting. And / or, the mold used for casting is a graphite mold, and the preheating temperature of the graphite mold is 200°C.

9. The preparation method according to claim 8, characterized in that, The deoxidation and slag removal process involves adding cryolite to the melt for deoxidation and slag removal, with the amount of cryolite added being 0.2 to 0.4% of the total mass of the melt.

10. A method for modifying a wear-resistant copper alloy reinforced with mixed grain whiskers, characterized in that the steps include... include: Prepare high-purity copper, high-purity nickel, high-purity silicon, sponge titanium, and Cu-20Sr master alloy as raw materials; Under argon protection and charcoal covering, the high-purity copper is smelted. After complete melting, high-purity nickel is added for the first heat preservation treatment. Then, it is cooled to the first preset temperature. High-purity silicon, sponge titanium and Cu-20Sr master alloy are added for the second heat preservation treatment. After the heat preservation is completed, deoxidation and slag removal treatment is performed, and Sr-modified granular whisker mixed reinforced copper alloy is cast. The composition of the Sr-modified granular whisker-reinforced copper alloy, by mass percentage, includes: Ni 1.0~6.0%, Si 0.2~1.5%, Ti 0.7~2% and Sr 0.01~0.20%, with the balance being Cu and unavoidable impurity elements.